2009
DOI: 10.1123/jpah.6.5.667
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Habitual Smoking on Measured and Predicted VO2max

Abstract: Background:Nonexercise models were developed to predict maximal oxygen consumption (VO2max). While these models are accurate, they don’t consider smoking, which negatively impacts measured VO2max. The purpose of this study was to examine the effects of smoking on both measured and predicted VO2max.Methods:Indirect calorimetry was used to measure VO2max in 2,749 men and women. Physical activity using the NASA Physical Activity Status Scale (PASS), body mass index (BMI), and smoking (pack-y = packs·day * y of sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 23 publications
(48 reference statements)
2
24
1
Order By: Relevance
“…[26], who observed highly significant correlations between measured VO 2max and the Heart Rate Ratio Method. Consistent with previous investigations, measured VO 2max was negatively associated with smoking [32]. In this study, only VPA in leisure-time contributed significantly to the regression model and showed a positive association with VO 2max .…”
Section: Discussionsupporting
confidence: 92%
“…[26], who observed highly significant correlations between measured VO 2max and the Heart Rate Ratio Method. Consistent with previous investigations, measured VO 2max was negatively associated with smoking [32]. In this study, only VPA in leisure-time contributed significantly to the regression model and showed a positive association with VO 2max .…”
Section: Discussionsupporting
confidence: 92%
“…Among girls this age, four in ten smoke, the highest prevalence in the world [78]. The smoking epidemic could also help to explain the relatively high prevalence of unhealthy fitness in the Chilean 8th graders, in particular among girls, given the adverse effect of smoking on both CRF [79] and MSF [80]. Furthermore, this high prevalence of smoking may be an indication of a broader attitude towards wellness in Chilean youth.…”
Section: Discussionmentioning
confidence: 99%
“…Hashizume et al (2000) reported 7 days of abstinence from smoking could improve exercise performance, and Suminski et al (2009) recommended that smoking should be considered when using non-exercise models to estimate maximal oxygen uptake. In the present study, maximal oxygen uptake was higher in non-smokers, and smoking was a significant variable in multiple regression analysis.…”
Section: Discussionmentioning
confidence: 99%